Analisis Faktor-Faktor Yang Mempengaruhi Jumlah Dana Pihak Ketiga Pada Bank Umum Syariah Di Indonesia (Periode Triwulan I 2010-Triwulan I 2015) - Wardati Mumtazah; Dina Fitrisia Septiarini (Universitas Airlangga, 2016)
The purpose of this research is to know whether the internal factors of Islamic Banks (profit sharing and bonus and promotion cost), and external factor of Islamic Banks (inflation) have significant effect, both simultaneously and partially, to the amount of third-party’s funds Islamic Bank in 1st quarterly of 2010 – 1st quarterly of 2015 period. The method used in this research is quantitative method and also using the secondary data which obtained from financial reports and other reports started from in 1st quarterly of 2010 – 1st quarterly of 2015. The population is Islamic Banks in Indonesia. The choosing of sample was done with using sampling purposive method and there are 6 Islamic Banks that comply with the specified sample criteria. Analysis technique used is multiple linier regression analysis of panel data.